KEMAJEMUKAN GEREJA DALAM BINGKAI PROMISSIO YANG MEMAKNAI MISSIO DAN COMPROMISSIO - Cahyono Budi Wibowo (Phronesis: Jurnal Teologi dan Misi, 2023)
The church is a visible fellowship of people from different cultures and plural societies in the name of Jesus. This is what is called the real church. Believing in the church means believing in the Lord Jesus' promise that when two or three people gather in His name, that is where He will be in the midst of them (Matthew 18:20). Believing in the church is believing that the church is a "sign" and "foretaste" of the fellowship between humans and God from His kingdom to come. This view of the church implies that the church has the characteristics of the presence of Jesus and the destiny of eschatology, as waiting for the kingdom to come, the church remains part of this world. It is marked by sin, unbelief, and division. For a structured approach, the author will use qualitative research to describe the situation and phenomenon of today's church pluralism which implies hidden problems and tensions between denominations within diversity. I will also use descriptive, correlational, and exploratory methods. This article closes with a church that must unite and understand that the church cannot alone but compromise in mission based on God's promises.